Determinants of using university canteens - Martins, Margarida (2013)
The present study aims to identify determinants of using university canteens. A randomly sample was selected from users of university canteens. A questionnaire was applied to canteen users during lunch period. Data collection involved socio-demographic and economic data of participants, reasons for using the canteen, determinants for searching for alternatives, as well as areas that need improvement in foodservice. University canteens are used, by most of surveyed students, with a frequency of 3 to 4 times per week, being the "social menu" the option mostly consumed. The location and cost of meals are the main reasons pointed by students for attending to the canteens. Furthermore, the limited variety of menus, along with the possibility of having meals at home and time spent, are the main factors that lead students looking for alternatives to the canteen. Several improvements were suggested such as increase menus variety and canteen sanitary conditions. Location, meal cost and opportunity for socialization were identified as main determinants for using university canteens. These results highlighted the need of offering quality and economic meals at university foodservices and providing pleasant environments well located for students' meals.